PENGARUH WORK FROM HOME TERHADAP WORK-LIFE BALANCE PEKERJA PEREMPUAN DI KOTA ENDE - Mea, Maria H. C. D; Hyronimus, Hyronimus (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Abstract:  The purpose of this study is to test the relationship between the application of Work from Home (WFH) to the Work-Life Balance (WLB) of female workers in the city of Ende who are married or single parents. This research was a quantitative research. The population and sample in this study were 50 female workers who worked from home during the early Covid-19 pandemic. Data collection was done by distributing questionnaires online. Data analysis was performed using the SMART PLS software version 3.0. R Square analysis results showed that Work from Home had a positive and significant effect of 67.5% on the Work-Life Balance of female workers in the city of Ende. F Square measurement results showed a value of 2,075 which means there was a strong influence between the variable Work From Home on Work-Life Balance. Statistical T value of 21,385 where larger T table (1.9846), showed a positive relationship between working from home with work-life balance. Keywords:     work from home, work-life balance, women, Ende, covid-19